CORE MUSCLE ASSESSMENT OF DANCERS - Viktoria KOVÁCSNÉ BOBÁLY; Alekszandra MAKAI; Gabriella KISS; Máte MARKUS; Katalin EKLICSNÉ LEPENYE; Ágnes SIMON-UGRON; Melinda JAROMI (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2016)
Background. To assess habitual postures as well as postures considered correct by dancers of different styles, and the intensity of their (low) back pain. To examine spinal functional status, strength and flexibility of core muscles necessary for correct posture and lumbar motor control skills. Our hypothesis is that lower back pain and deviation in the functional status of the spine are more common among dancers aged 9-18 than in the average population, or other sportsmen. Despite regular trainings, weakness is observed in muscles needed for correct posture. Methods. Our survey sample consists of members of three different dance genres. Groups examined include a classic ballet, a hip-hop dance and a ballroom dance group (n=92, mean age:14.15± 2.96). Examination of habitual postures and postures considered correct was performed by a photogrammetric test, while the intensity of low back pain was measured by a visual analogue scale, and the Roland-Morris questionnaire. Lumbar motor control skills were examined by sitting forward lean test and the strength of core muscles by the core test. Results. In posture analysis significant difference was found in anterior view of the posture considered correct; ballroom dancers showed significantly better posture (p=0. 038), than the other two groups examined. During the examination of low back pain intensity by a visual analogue scale ballroom dancers reported about the negative effect of pain on performance to a significantly higher degree (p=0.019). Core test demonstrated significantly better core muscle strength among ballroom dancers (p=0.000), than in the other two groups. Conclusion. Neither habitual, nor the posture considered correct of the dancers meet the requirements of the biomechanically correct posture. Low back pain manifests at an early age among dancers affecting their performance. Lumbar motor control skills and core muscle strength are inadequate despite regular exercise.